Testing and Analysis of PIM Performance in a Passive DAS Network - Experimental Approach - Muhammed Abudu Aniru; Emagbetere Joy Omoavowere (Universitas Komputer Indonesia, 2025)
This study investigates Passive Intermodulation (PIM) levels within a passive distributed antenna system (DAS) for cellular networks across a multi-floor building. PIM significantly degrades network performance if unaddressed during deployment. Using an experimental approach, on-site testing was conducted on a multicarrier system (700–2600MHz) using Kaelus PIM analyzers. Tests strictly followed industry standards with high RF power configurations. Test points included vertical and horizontal cabling against a -150dBc baseline. Analysis focused on time-domain PIM traces and the impact of altering two-tone signal frequencies on the IM3 component. The findings emphasize selecting frequencies away from band edges to avoid interference. Resolution measures based on pass/fail outcomes effectively mitigated PIM, ensuring optimal signal integrity and network reliability